Belantamab Mafodotin Monotherapy for Multiply‐Relapsed Myeloma: A Retrospective Study From the United Kingdom and the Republic of Ireland - Edmund C. R. Watson; Faouzi Djebbari; Fotios Panitsas; Grant Vallance; Samir Asher; Malahat Saeed; Mairi Walker; Matthew Powell; Alexandros Rampotas; Heather Leary; Akhil Khera; Angharad Atkinson; et al. (eJHaem)
ABSTRACT Introduction Belantamab mafodotin (belamaf) was the first BCMA‐targeting immunotherapy licensed in myeloma and was available as monotherapy for a fifth or greater line of treatment. Outcomes for patients in the United Kingdom and the Republic of Ireland potentially differ from those of other regions and may illuminate factors predicting response to therapy. Methods and Results We performed a retrospective study of patients treated with belamaf monotherapy in the United Kingdom and the Republic of Ireland. In our cohort of 88 patients, we saw an overall response rate (ORR) of 60%, a median progression‐free survival (PFS) of 8.7 months and a median duration of response (DoR) of 15.8 months. The spectrum of adverse events was as expected, with 84% (71/85) of patients experiencing toxicity. Eye‐related adverse events were the most common, affecting 66% (56/85), leading to dose reduction or delay in 41% (35/85) and discontinuation in 6% (5/85). We specifically assessed physician decision‐making in the context of ocular side effects and found a relatively high frequency of the drug being administered despite moderate levels of toxicity. Conclusion Our cohort's ORR is significantly different from those of the DREAMM‐2 and ‐3 trials and other real‐world studies, though a long‐duration response has been reported in other cohorts. Comparative analysis with other real‐world studies did not reveal any significant factors predictive of ORR. The frequent administration of belamaf to patients with eye disease may well reflect a more pragmatic approach than was originally prescribed in the landmark trials. Trial Registration The authors have confirmed clinical trial registration is not needed for this submission.